Investigating Algerian University EFL Teachers’ and Students’ Perceptions Regarding the Use and Impact of Digital Devices on Speaking Proficiency - MINH, Ayad abdoulmunem; BELOUAHEM, Riad (Journal of Human Sciences, 2025)
This study explores the impact of digital devices on speaking skill and their integration into language learning. Findings show that freshmen rely heavily on smartphones, the internet, computers, and tablets for academic purposes. A questionnaire was conducted with 65 first-year English students at Abou EL Kacem Saâdallah, Algiers 2 University, followed by interviews with ten university teachers. The study highlights technology’s crucial role in academic success, enhancing speaking skills, proficiency, and pronunciation. Teachers confirm frequent student use of language learning apps, social media, and video platforms, with smartphones as the primary tool. They acknowledge benefits such as exposure to native speakers and vocabulary-rich content but emphasize student engagement. While digital tools significantly improve speaking skills, their impact on writing and listening is less evident. Both students and teachers recognize technology’s positive influence on language learning, particularly in developing speaking abilities.